ANALISIS KEBIJAKAN DEVIDEN SEBELUM DAN SESUDAH UU OMNIBUS LAW CIPTA KERJA DIBERLAKUKAN DI ERA NEW NORMAL - Susilawati; Ameilia Damayanti; Sri Ambarwati; Gabriella (RELEVAN : Jurnal Riset Akuntansi, 2021)
This study aims to find out if there are differences in dividend policies before and after the Omnibus Law on Job Creation was enacted in the new normal era. The variable used in this study is the dividend policy as measured by the dividend payout ratio. The sample used in this study are pharmaceutical and food and beverage industry companies listed on the Indonesia Stock Exchange, published financial reports in 2017 - 20120 with 19 sample companies using the purposive sampling method. The results of the study show that there are differences in dividend policies in the pharmaceutical, food and beverage industry in the period before the new normal or before the provisions of the Omnibus Law in Job Creation were enacted in Indonesia, namely lower dividend payments or policies. Then there are differences in dividend policies in the pharmaceutical, food and beverage industries in the period after the new normal or after the provisions of the Omnibus Law Employement Law are enacted in Indonesia, namely higher dividend payments or policies